Characteristics and outcomes of patients with COVID‐19 admitted to ICU in a tertiary hospital in Stockholm, Sweden. Issue 1 (15th September 2020) - Larsson, Emma; Brattström, Olof; Agvald‐Öhman, Christina; Grip, Jonathan; Campoccia Jalde, Francesca; Strålin, Kristoffer; Nauclér, Pontus; Oldner, Anders; Konrad, David; Persson, Björn P.; Eriksson, Lars I.; Mårtensson, Johan; et al.
Abstract: Background: Information on characteristics and outcomes of intensive care unit (ICU) patients with COVID‐19 remains limited. We examined characteristics, clinical course and early outcomes of patients with COVID‐19 admitted to ICU. Methods: We included all 260 patients with COVID‐19 admitted to nine ICUs at the Karolinska University Hospital (Stockholm, Sweden) between 9 March and 20 April 2020. Primary outcome was in‐hospital mortality among patients with definite outcomes (discharged from ICU or death), as of 30 April 2020 (study end point). Secondary outcomes included ICU length of stay, the proportion of patients receiving mechanical ventilation and renal replacement therapy, and hospital discharge destination. Results: Of 260 ICU patients with COVID‐19, 208 (80.0%) were men, the median age was 59 (IQR 51‐65) years, 154 (59.2%) had at least one comorbidity, and the median duration of symptoms preceding ICU admission was 11 (IQR 8‐14) days. Sixty‐two (23.8%) patients remained in ICU at study end point. Among the 198 patients with definite outcomes, ICU length of stay was 12 (IQR, 6‐18) days, 163 (82.3%) received mechanical ventilation, 28 (14.1%) received renal replacement therapy, 60 (30.3%) died, 62 (31.3%) were discharged home, 47 (23.7%) were discharged to ward, and 29 (14.6%) were discharged to another health care facility. On multivariable logistic regression analysis, older age and admission from the emergency department was associated with higher mortality. Conclusion: This study presents detailed data on clinical characteristics and early outcomes of consecutive patients with COVID‐19 admitted to ICU in a large tertiary hospital in Sweden.